Contribution of Religious Leaders in Behavioral Education in Adolescents - Dollah, Hajjah Sri Rahayu Nurjanah binti Haji; Ulfah, Farida (FOCUS, 2023)
This research departs from the problem of adolescent ethics which is very concerning, where teenagers who used to be polite but now have less ethics (morals), teenagers now speak harsh words that have become commonplace, even reluctant to participate in religious activities. such as recitation and ethics education provided by religious leaders to the community, youth, and young children. This study aims to find out what perceptions exist in society about the role of religious leaders in adolescents, to determine the contribution of religious leaders in shaping behavior in adolescents, to determine the condition of adolescent behavior in Tanjungbaru Village, Cikarang Timur Bekasi. This research is a descriptive study using a qualitative approach. Data collection techniques in this study used observation and interviews, supplemented by secondary data in the form of reference books, as well as previous research relevant to the research theme to support data in the field. This study uses the theory of structural functionalism from Talcott Parsons about change. The findings of this study are regarding the Contribution of Religious Leaders in Behavioral Education for Adolescents. A Descriptive Study of Ethics Education for Adolescents in Tanjung Baru Village, Kec. East Cikarang Regency. Bekasi, based on research results the contribution made by religious figures in behavioral (ethical) education to adolescents is by (1) establishing Islamic boarding schools, (2) mosque youth bonds (IRMAS), (3) exemplary, (4) direct advice or lectures.